A quantitative objective method for the evaluation of anti-sperm cell-mediated immunity in humans - Dimitrov, D G; Sedlák, R; Nouza, K; Kinský, R (Journal of immunological methods, 1992)
Anti-sperm cell-mediated immunity (CMI) is considered as a crucial facet of infertility in patients of both sexes. A precise and objective method is designed, based on a one-step agarose leukocyte migration inhibition factor (LMIF) assay. The migration areas are evaluated by a computer-assisted image analysis system. Optimal concentrations of leukocytes and sperm, as well as technical conditions are described. The radial migration indexes (RMI) and area migration indexes (AMI) are computed and expressed as a migration index (MI) percentage for each patient or control. Preliminary clinical results indicate a highly significant association between migration inhibition and cases of 'immunopathological infertility'. The method described is considered a promising tool for a rapid and quantitative evaluation of a suspected anti-sperm CMI in infertile and recurrently aborting patients.
Keywords: Immunity, Cellular; spermie; ženská infertilita; Autoimmunity; Infertility, Female; Spermatozoa; autoimunita; Male; Cell Migration Inhibition; buněčná imunita; lidé; mužské pohlaví; ženské pohlaví; inhibice migrace buněk; Female; Humans; mužská infertilita; Infertility, Male